Field Analysis of Biological Factors Associated With Sites at High and Low to Moderate Risk for Eastern Equine Encephalitis Virus Winter Activity in Florida. Issue 6 (24th April 2021) - Miley, Kristi M; Downs, Joni; Burkett-Cadena, Nathan D; West, Richard G; Hunt, Brenda; Deskins, George; Kellner, Billy; Fisher-Grainger, Sandra; Unnasch, Robert S; Unnasch, Thomas R
Abstract: Eastern equine encephalitis virus (EEEV) is the most pathogenic arbovirus endemic to the United States. Studies have demonstrated Florida's role as a regional reservoir for the virus and its ability to support year-round transmission. Previous research has developed risk index models for mapping locations most at risk for EEEV transmission. We compared vector abundance, vector feeding behavior, potential host species, and fauna presence at high versus low–moderate risk sites during the winter and spring. Predicted high-risk sites had a significantly greater abundance of mosquitoes overall, including Culiseta melanura (Coquillett) (Diptera: Culicidae), the primary enzootic vector of EEEV. Twenty host species were identified from Cs. melanura bloodmeals, with the majority taken from avian species. Culiseta melanura largely fed upon the Northern Cardinal ( Cardinalis cardinalis (Passeriformes: Cardinalidae)), which accounted for 20–24.4% of the bloodmeals obtained from this species in years 1 and 2, respectively. One EEEV-positive mosquito pool ( Cs. melanura ) and nine EEEV seropositive sentinel chickens were confirmed during winter-spring collections from high-risk sites; no seropositive chickens nor mosquito pools were found at the low–moderate risk sites. These results suggest that high-risk sites for EEEV activity are characterized by habitats that support populations of Cs. melanura and which may also provide ample opportunities to feed upon Northern Cardinals. The overall low level of mosquito populations during the winter also suggests that control of Cs. melanura populations in winter at high-risk sites may prove effective in reducing EEEV transmission during the peak summer season.